Law Enforcement Against Violent Theft Perpetrated by Children: A Study at the North Sumatra Regional Police - Gabriella Pasaribu; Haposan Siallagan; Ojak Nainggolan (Sultan Agung Notary Law Review, 2026)
This study aims to analyze law enforcement against perpetrators of violent theft committed by minors in the North Sumatra Regional Police jurisdiction. The phenomenon of juvenile delinquency involving violent crimes such as violent theft is a social problem that is becoming increasingly complex and requires serious attention from various parties, especially law enforcement officials. This study uses an empirical juridical approach with primary data obtained through in-depth interviews with the police, prosecutors, courts, and relevant stakeholders in North Sumatra. Data collection techniques were carried out using purposive sampling of key informants who have direct understanding of the handling of violent theft cases involving child perpetrators. The results show that law enforcement against juvenile perpetrators of violent theft in North Sumatra faces various challenges, ranging from legal and social aspects to rehabilitation. On the other hand, the limited facilities for empowerment and social reintegration for juvenile offenders also pose obstacles to the application of restorative justice principles. This study recommends the need for a balanced approach between retributive and restorative aspects in handling cases of children who commit violent crimes, as well as increased coordination between law enforcement and social welfare agencies in efforts to prevent and handle violent crimes committed by minors.